Long‐term outcomes of combining prostate brachytherapy and metastasis‐directed radiotherapy in newly diagnosed oligometastatic prostate cancer: A retrospective cohort study. Issue 5 (26th December 2018) - Tsumura, Hideyasu; Ishiyama, Hiromichi; Tabata, Ken‐ichi; Sekiguchi, Akane; Kawakami, Shogo; Satoh, Takefumi; Kitano, Masashi; Iwamura, Masatsugu
Abstract : Background: Systemic Therapy in Advancing or Metastatic Prostate Cancer: Evaluation of Drug Efficacy (STAMPEDE) trial showed the survival benefit for prostate radiotherapy in newly diagnosed prostate cancer patients with a low metastatic burden. The result raises the next question whether additional radiotherapy to metastatic sites could improve the survival in those with a low metastatic burden. Methods: We evaluated the efficacy and safety of prostate‐directed radiotherapy (PDRT) with or without metastasis‐directed radiotherapy (MDRT) in newly diagnosed oligometastatic patients who underwent combination of high‐dose‐rate prostate brachytherapy, external beam radiotherapy, and androgen deprivation therapy. Forty patients with bone metastasis and node positive prostate cancer were retrospectively analyzed. Of these, 22 (55%), 3 (7%), and 15 (38%) patients had N1M0, M1a, and M1b, respectively. Eighteen patients (45%) received MDRT to all metastatic sites. All patients initially underwent ≧6 months of androgen deprivation therapy. Oligometastatic disease was defined as presence of five or fewer metastatic lesions. Median follow‐up period was 62.5 months. Results: Of the 40 patients, the 5‐year castration‐resistant prostate cancer (CRPC)‐free survival rate and cancer‐specific survival was 64.4% and 87.9%, respectively. Pre‐ or post‐treatment predictive value including prostate‐specific antigen (PSA) at diagnosis ≥20 ng/mL, Gleason grade group 5, positive biopsy core rate ≥51%, PSA nadir level of ≥0.02 ng/mL after the radiotherapy, and no MDRT were significantly associated with progression to CRPC. Patients with MDRT had significantly higher probability of achieving a PSA level of <0.02 ng/mL than those without the therapy (88.8% vs 54.5%, P  = 0.0354) and consequently had a better CRPC‐free survival than those without the therapy (HR 0.319, 95%CI: 0.116‐0.877). Comparing PDRT alone, PDRT with MDRT did not significantly increase the incidences of genitourinary and gastrointestinal toxicities. Conclusions: This single‐institutional study revealed the feasibility of combining prostate brachytherapy and MDRT for newly diagnosed oligometastatic prostate cancer. This combined approach has potential to prolong CRPC‐free survival.